2019
DOI: 10.1186/s13578-019-0298-7
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Cpf1 proteins: structure, function and implications for genome editing

Abstract: CRISPR and CRISPR-associated (Cas) protein, as components of microbial adaptive immune system, allows biologists to edit genomic DNA in a precise and specific way. CRISPR-Cas systems are classified into two main classes and six types. Cpf1 is a putative type V (class II) CRISPR effector, which can be programmed with a CRISPR RNA to bind and cleave complementary DNA targets. Cpf1 has recently emerged as an alternative for Cas9, due to its distinct features such as the ability to target T-rich motifs, no need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(99 citation statements)
references
References 160 publications
(240 reference statements)
0
99
0
Order By: Relevance
“…It has been considered more effective than HDR‐mediated base‐pair substitution . To date, several base editing systems, for instance BE3, BE4, Targeted‐AID, and dCpf1‐BE have been used in various organisms including major crops. These systems utilize Cas9 or Cpf1 systems for recruiting cytidine deaminases, which generate specific C–T alterations by using DNA mismatch repair pathways …”
Section: E‐crisp/cas Systemsmentioning
confidence: 99%
“…It has been considered more effective than HDR‐mediated base‐pair substitution . To date, several base editing systems, for instance BE3, BE4, Targeted‐AID, and dCpf1‐BE have been used in various organisms including major crops. These systems utilize Cas9 or Cpf1 systems for recruiting cytidine deaminases, which generate specific C–T alterations by using DNA mismatch repair pathways …”
Section: E‐crisp/cas Systemsmentioning
confidence: 99%
“…In this study, one important application of DocMF was to quickly and accurately identify the PAMs of any Crispr-Cas system (Figure 3-4). The Crispr-Cas system was initially identified in the prokaryotic immune system and was quickly adopted as a reliable genome engineering tool (24) (31). The PAM sequence is adjacent to the target site and is essential for Cas endonuclease specificity.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the number of potential genome editing sites, we are in urgent need of new Cas (that recognize PAM sequences beyond the commonly used 5'-NGG-3' site for SpCas9 (16). DocMF could be a very useful tool for characterizing the novel Cas protein PAM sequences with the following advantages: 1) a universal system for different Crispr-Cas systems, with the same DNB pools PAMs, a single guide RNA, and the production of a staggered DNA double-stranded break (31). Our characterization of VeCas9 and BvCpf1 helps to expand the existing CRISPR toolbox and provide more promising candidates for genome engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Cpf1 endonuclease derived from Acidaminococcus sp. BV3L6 and Lachnospiraceae ND2006 bacteria, it was found that the effect of this system on eukaryotic cells is compatible with the CRISPR-Cas9 [38]. However, functional Cpf1 does not require the tracrRNA, but crRNA is needed.…”
Section: Crispr-cpf1(cas12)mentioning
confidence: 95%